Strategi Penerapan Lean Manajemen dalam Upaya Mengoptimalkan Proses Pelayanan Pasien Rawat Inap di RSUD Datu Pancaitana Kabupaten Bone - Risna Fitriana Amusroh; Erliany Syaodih; Yuniati Lestari (Lembaga Pengembangan Kinerja Dosen, 2025)
Along with the introduction of the National Health Insurance (JKN) system which began on January 1, 2014, the Indonesian health system is facing increasing challenges with the increasing demand for public services, these services are required to improve accountability and quality of service. Healthcare institutions globally have attempted to adopt the Lean management methodology which aims to improve operational efficiency and overall effectiveness. This is greatly needed with the increasing number of patients being treated in hospitals, this means an increase in the number of patient service activities in the inpatient room, in addition to the increasing need for other resources such as human resources and hospital infrastructure. The purpose of this study is to analyze the inefficiencies in the service process and the use of resources in the inpatient room that have an impact on service quality so that hospitals can create solutions by redesigning processes, controlling waste, and improving workflows using Value Stream Mapping (VSM) analysis. The population in this study was the inpatient service process of Melati RSUD Datu Pancaitana and the research sample was all inpatient nurses of Melati and selected inpatients. This type of research is qualitative descriptive research. Data collection techniques were observation, interviews, questionnaires, field notes, and document reviews. Based on the results of the study, it showed that the flow or process with the most waste value was waste waiting and waste overprocessing, the efficiency level reached 77.7% after the implementation of lean by carrying out the designed added value activities, although in its implementation it faced challenges in the form of process complexity, limited resources, diverse waste, to organizational resistance and technological limitations.